Consumerismo e consumidores indignados: netativismo contra as marcas nas redes sociais - Borges, Fábio Mariano (2017)
Digital activism or netativism is a recent advent and expression of the political exercise of users of the cyber world, especially of social networks. One of its types refers to the manifestations of the consumers against the companies through denunciations of crimes and attempt to promote boycott against them, in order to positive results for the collective. In this sense, consumption is seen as an area to political exercise, and this type of practice is even more democratized and accessible through social networks. The present study reflects about the reconfiguration of consumerism, very recently impacted by consumer netativism. Consumerism is a sociological term that names the set of consumer practices in order to exercise power, conquest, maintenance of rights and resistance to the commercial interests of the companies. The object of research is the manifestations of consumer indignation on Facebook between the years 2012 and 2017. For that, was conducted netnography, through monitoring the clashes between consumers and businesses on Facebook. In this sense, the study analyzes consumerism in the form of netativism, as a device of power, as well as consumption, both situated in the concept of biopolitics developed by Foucault